â€œBASINTOJIKâ€ BERSUMBER DARI KESENIAN â€œCALEMPONG RARAK GODANGâ€ DI KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - Azrizer Azrizer; Asep Saepul Haris; Arnailis Arnailis (Jurnal Musik Etnik Nusantara, 2024)
The composition "Basintojik" is a musical composition inspired by the art of calempong rarak godang which was born and developed in the Kuantan Singingi Regency, Riau Province. This art is usually performed at various traditional events and important ceremonies, such as weddings, religious celebrations, silek, and processional music at track events. Calempong rarak godang has several repertoires including Kedidi, Tigo-tigo, Ciek-ciek, Tak tendut, Gelang-gelang, Kacimpuang, Gamiak-gamiak and Pik tontong. The results of the artist's analysis of the art of Calempong Rarak Godang found that the beginning of each song always has the same rhythm pattern and also every Calempong Rarak Godang repertoire always ends using the same ending melody (bonti) using meter three or a 3/4 melody pattern. The principle of the bonti melody, which is always the same, became the basic idea in the work which was done using the World Musik approach, giving birth to a new composition entitled "Basintojik".